THE EFFECT OF THE NUMBER OF POOR POPULATION, EDUCATION LEVEL, AND REGIONAL ORIGINAL REVENUE (PAD) ON ECONOMIC GROWTH OF REGENCIES/CITIES IN BALI PROVINCE - I Dewa Bagus Agung Satria Indra Putra; Amrita Nugraheni Saraswaty (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
One of the serious problems faced by Indonesia is economic growth. Economic growth is a condition in which there is development of activities in the economy, indicated by an increase in the production of goods and services as well as an improvement in public welfare. The success of regional development can be observed from the level of economic growth. This study uses a quantitative and associative approach, which aims to determine the relationship between two or more variables. This study aims to examine the relationship among several variables, namely the direct effect of the number of poor population, education level, and Regional Original Revenue (PAD) on economic growth, as well as the indirect effect of the number of poor population, education level, and Regional Original Revenue (PAD) on economic growth. The variable of the number of poor population (X1) does not have a negative effect on the economic growth variable (Y). The education level variable (X2) has a positive effect on the economic growth variable (Y). The education level variable (X2) has a positive effect on the economic growth variable (Y). (1) The number of poor population, education level, and Regional Original Revenue (PAD) simultaneously have a significant effect on the economic growth of regencies/cities in Bali Province. (2) The number of poor population partially has a negative and insignificant effect on the economic growth of regencies/cities in Bali Province, while education level and Regional Original Revenue (PAD) partially have a positive and significant effect on the economic growth of regencies/cities in Bali Province.